2007
DOI: 10.1007/s11589-007-0656-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic tidal parameters for gravity over China and its neighbor area

Abstract: The synthetic tidal parameters with high spatial resolution for gravity over China and its neighbor area are constructed with Earth's tidal model and ocean tide loading calculated using TPXO7 global ocean tide model as well as tidal data over China seas. The comparison between synthetic parameters and ones observed by spring gravimeters at some seismic network stations and Hong Kong station and one observed by super-conducting gravimeter at Wuhan station shows that the average differences in amplitude factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Zhou et al pointed out that it was necessary to adopt higher resolution and constructed tidal parameters for gravity in China and its neighbor area with spatial resolution of 0.25 • by using the same method as Zahren's. The results showed that the constructed tidal parameters were in good agreement with the observed ones [32,34] . In order to obtain correction model with high accuracy, it is necessary to take the secondary constituents into consideration, especially the ones whose frequencies are closer to the eigenfrequency of Earth's NDFW.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Zhou et al pointed out that it was necessary to adopt higher resolution and constructed tidal parameters for gravity in China and its neighbor area with spatial resolution of 0.25 • by using the same method as Zahren's. The results showed that the constructed tidal parameters were in good agreement with the observed ones [32,34] . In order to obtain correction model with high accuracy, it is necessary to take the secondary constituents into consideration, especially the ones whose frequencies are closer to the eigenfrequency of Earth's NDFW.…”
Section: Introductionsupporting
confidence: 81%
“…Because the ocean tidal height and its phase from ocean tide model are not comprised of geodetic coefficients which are used in solid earth tides and have +/-sign in different areas, and because the amplitude is always defined positive, the sign of geodetic coefficients will induce phase shift of 180 • when summing solid earth tides and ocean tide loading effects to obtain tidal parameters through Eq. (4) below in some area [32] .…”
Section: Construction Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the population density measure proposed by Zhou [51], the core explanatory variable population density is equal to the resident population/built-up area of the district or county. Among them, the existing statistical yearbooks in China cannot provide robust built-up area data for consecutive years [41].…”
Section: Data Sourcesmentioning
confidence: 99%
“…Urban territorial boundaries can be divided into three categories, namely administrative, functional, and physical territories. Among them, the physical territory best expresses the territorial scope of the city [16]. On this basis, many scholars have used various methods to try to identify the territorial extent of the city.…”
Section: Introductionmentioning
confidence: 99%